An exploration of the relationship between cultural and informational diversity and innovation; A case study of MultiChoice South Africa - Morgan, Kelly-Anne (My University, 2016)
This research was conducted to gain insights about the current perceptions of the value of diversity in the context of creativity and innovation within the video on demand division in MultiChoice. Although many existing studies have produced mixed results when attempting to determine the value of certain types of diversity and their effects on creativity within work groups or teams within an organisation in either Western or European contexts, the amount of research focused on diversity and its effects on creativity within South African organisations are sparse. Previous studies regarding the types of diversity that are most valuable for enhancing work group’s capacity for creativity and by extension innovation were used as frameworks for guiding this research. Primary research highlighted that in the context of innovation cultural and informational diversity have been shown to produce the most notable results on work group performance. Therefore this study focused on two types of diversity and their effects on work groups and the value of these types of diversity from an HOD perspective. The data revealed that of the two types of diversities examined, informational diversity was noted to have more value with regard to creativity and innovation than that of cultural diversity. Although cultural diversity was considered valuable for innovation to an extent, majority of the participants offered reasons as to why they deemed informational diversity to be of more value in terms of innovation. Cultural diversity was found to be valuable for correcting the injustices of the past but the negative effects on work group performance deemed this type of diversity to be less valuable in comparison to informational diversity within this division. A series of moderators was established by the participants which act as tools for facilitating the relationship between the different types of diversity and their effects on creativity within work groups. This research was conducted in the hope that the broader organisation would make use of these findings to adjust their diversity strategies for the purposes of enhanced creativity and innovation. The researcher was of the idea that cultural diversity would outweigh any other type of diversity based on South Africa’s rich cultural diversity and the presence of this type within the division being studied. However, this was disproven by the findings of this study. A series of in-depth interviews was conducted with each HOD in the division. The findings of this study will contribute to existing research in this field by highlighting the perceptions of cultural diversity based on South Africa’s history and how this affects the perceived value of cultural diversity within workgroups. The outcomes of this study while specific to the division in which the study occurred can be generalised to the extent to which it can provide a framework for other South African organisations to evaluate cultural and informational diversity against. Furthermore, tools for moderating the negative effects of cultural diversity and informational diversity were offered by the participants but these have yet to be tested. Nevertheless, these moderators were key findings based on the participants’ experience with both cultural and informational diversity within their respective work groups.
Keywords: Diversity; Diversity value; Cultural diversity; Informational diversity; Work group performance